Player Types, Motivations & The Western Australian Live Action Role-Play Community: An investigation of Possible LARP Player & Digital Game Theory Compatibility - Meakins, Ryan James (Curtin University, 2022)
This thesis aimed to investigate the extent to which Bartle’s (1996) Multi-User Dungeon (MUD) player taxonomy can be applied to the classification of the motivations of the Western Australian Live Action Role-Play (LARP) community. This work resulted in the production of the refined LARPer Motivation Typology theory which can provide a greater understanding of the motivational behaviours of WA LARP participants for the benefit of scholarly researchers, LARP Organisers and individual LARP players.